Violent night [videorecording (DVD)] - Casey, Patrick, 1978-; Miller, Joshua, 1978-; Weston, Matthew, 1983-; Lewis, Dominic; Harbour, David, 1975-; Leguizamo, John; Hassell, Alex, 1980-; Louder, Alexis; Patterson, Edi, 1974-; Gigandet, Cam, 1982-; Brady, Leah; D'Angelo, Beverly (Universal, 2023)
A group of mercenaries attack the estate of a wealthy family on Christmas Eve, and Santa must save Christmas.